DESIGN AND ANALYSIS OF HELIUM BRAYTON CYCLE FOR ENERGY CONVERSION SYSTEM OF RGTT200K - Ignatius Djoko Irianto (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2016)
ABSTRACTDESIGN AND ANALYSIS OF HELIUM BRAYTON CYCLE FOR ENERGY CONVERSION SYSTEM OF RGTT200K. The helium Brayton cycle for the design of cogeneration energy conversion system for RGTT200K have been analyzed to obtain the higher thermal efficiency and energy utilization factor. The aim of this research is to analyze the potential of the helium Brayton cycle to be implemented in the design of cogeneration energy conversion system of RGTT200K. Three configuration models of cogeneration energy conversion systems have been investigated. In the first configuration model, an intermediate heat exchanger (IHX) is installed in series with the gas turbine, while in the second configuration model, IHX and gas turbines are installed in parallel. The third configuration model is similar to the first configuration, but with two compressors. Performance analysis of Brayton cycle used for cogeneration energy conversion system of RGTT200K has been done by simulating and calculating using CHEMCAD code. The simulation result shows that the three configuration models of cogeneration energy conversion system give the temperature of thermal energy in the secondary side of IHX more than 800 oC at the reactor coolant mass flow rate of 145 kg/s. Nevertheless, the performance parameters, which include thermal efficiency and energy utilization factor (EUF), are different for each configuration model. By comparing the performance parameter in the three configurations of helium Brayton cycle for cogeneration energy conversion systems RGTT200K, it is found that the energy conversion system with a first configuration has the highest thermal efficiency and energy utilization factor (EUF). Thermal efficiency and energy utilization factor for the first configuration of the reactor coolant mass flow rate of 145 kg/s are 35.82% and 80.63%.Keywords: Helium Brayton cycle, RGTT200K, Energy conversion system, EUF, Efficiency, ABSTRAKANALISIS DAN DESAIN SIKLUS BRAYTON HELIUM UNTUK SISTEM KONVERSI ENERGI RGTT200K. Telah dilakukan analisis siklus Brayton helium pada desain sistem konversi energi kogenerasi RGTT200K untuk memperoleh tingkat efisiensi termal dan faktor pemanfaatan energi yang tinggi. Tujuan penelitian ini adalah untuk menganalisis potensi siklus Brayton helium untuk diterapkan dalam desain sistem konversi energi kogenerasi RGTT200K. Tiga model konfigurasi desain sistem konversi energi kogenerasi telah dianalisis. Pada model konfigurasi pertama Intermediate Heat Exchanger (IHX) dipasang secara serial dengan turbin gas, sedangkan pada model konfigurasi kedua IHX dan turbin gas dipasang secara paralel. Model konfigurasi ketiga mirip dengan konfigurasi pertama, tetapi pada model konfigurasi ketiga dipasang dua kompresor. Analisis kinerja pada desain siklus Brayton untuk sistem konversi energi RGTT200K dilakukan dengan cara simulasi dan perhitungan kinerja sistem konversi energi menggunakan kode komputer CHEMCAD. Hasil simulasi menunjukkan bahwa ketiga model konfigurasi dapat memberikan energi termal pada sisi sekunder IHX dengan temperatur lebih dari 800 oC jika laju aliran massa pendingin reaktor 145 kg/s. Namun demikian, paremeter kinerja yang meliputi efisiensi thermal dan faktor pemanfaatan energi (EUF) berbeda untuk masing-masing model konfigurasi. Hasil perbandingan parameter kinerja pada ketiga model konfigurasi siklus Brayton helium untuk sistem konversi energi kogenerasi RGTT200K menunjukkan bahwa model konfigurasi sistem konversi energi kogenerasi yang pertama memiliki efisiensi termal dan faktor pemanfaatan energi (EUF) tertinggi. Nilai efisiensi termal dan faktor pemanfaatan energi untuk model konfigurasi pertama dengan laju aliran massa pendingin reaktor 145 kg/s adalah 35,82% dan 80,63%. Kata kunci: Siklus Brayton helium, RGTT200K, Sistem konversi energi, EUF, EfisiensiKeywords : Helium Brayton cycle, RGTT200K, Energy conversion system, EUF, Efficiency,